(untitled) (Harmoni, 2012)
Fundamentalist in Religious movement of students at the campus of STAIN Metro Lampung started from emerging of campus religious dissemintaion movement (LDK). This institute is a student organisation which active in various religius activities. Prae-survey data on many activities done by LDK Al Ishlah, shows that this organisation always invite many mentors from organizations that are networks with Moslem fundamentalists in Indonesia. The understanding system on religion of the LDK activist has been such a truth claims, which implies to formation of mode of thought in kind of particularistic and exclusive. This study explore typology and patterns of studentss` activities. Beside, this study also traced various causal factors of spread of this kind activies among students at the campus.